2004
DOI: 10.1128/jcm.42.12.5604-5608.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profile of an Oka Varicella Vaccine Virus Variant Isolated from an Infant with Zoster

Abstract: Varicella (chickenpox) is a widespread, highly contagious disease caused by varicella-zoster virus (VZV). Serious complications of varicella include secondary bacterial infection, pneumonia, encephalitis, congenital infection, and, rarely, death (4, 21). Following the acute infection, VZV establishes a lifelong latent infection in neurosensory ganglia that commonly reactivates to cause zoster, typically in elderly or immunocompromised patients (24). A safe and effective live-attenuated varicella vaccine was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 25 publications
3
32
1
Order By: Relevance
“…Comparison of the four Oka strain sequences of VZV indicated that Oka-V GSK is genetically closer to Oka-V than Oka-V Merck is but that Oka-V Merck is closer to Oka-P than Oka-V GSK is (reference 50 and the present study). In agreement with these findings, Sauerbrei et al demonstrated that Oka-V Merck is genetically closer to Oka-P than Oka-V GSK is (59). Nevertheless, it is well established that both vaccine strains are attenuated but remain strongly immunogenic (43,73).…”
Section: Continued On Following Pagesupporting
confidence: 60%
See 1 more Smart Citation
“…Comparison of the four Oka strain sequences of VZV indicated that Oka-V GSK is genetically closer to Oka-V than Oka-V Merck is but that Oka-V Merck is closer to Oka-P than Oka-V GSK is (reference 50 and the present study). In agreement with these findings, Sauerbrei et al demonstrated that Oka-V Merck is genetically closer to Oka-P than Oka-V GSK is (59). Nevertheless, it is well established that both vaccine strains are attenuated but remain strongly immunogenic (43,73).…”
Section: Continued On Following Pagesupporting
confidence: 60%
“…Comparison with partial sequencing information published on these strains and the other Oka strains, Oka-P and Oka-V, is shown in Table 7 (3,22,32,59,60,63,69 (3,60). Two sequence differences were found for Oka-V Merck in ORF 59 (position 101089; A versus A/G) and ORF 62 (position 105310; G versus A/G) (3).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Varivax lots revealed VZV strains with pure vaccine types at these positions (13,14). These data and those presented here show that the mixtures of variant strains in the vaccines as well as the relative strain proportions change with time in different vaccine batches.…”
Section: Vol 18 2011 Molecular Analysis Of Vzv From Vaccines and Vacontrasting
confidence: 35%
“…Second, vaccine-type VZV strains causing rash-associated clinical syndromes in vaccinees have been reported to contain a number of wild-type (wt) SNPs. It has been hypothesized that these vaccine-type, wt SNP-containing VZV strains are minor components of the vaccines (1,9,10,13). To substantiate this hypothesis and to search for genetic correlates of the observed differences among the vaccines, we compared the SNP profiles of (i) VZV from the three vaccine brands, (ii) rash-associated vaccine-type VZV from German vaccinees, and (iii) wt VZV from nonvaccinated and vaccinated individuals suffering from varicella by PCR, quantitative pyrosequencing (PSQ), and chain termination sequencing (CTSQ).…”
mentioning
confidence: 99%
“…All of the currently available varicella vaccines consist of an avirulent virus derived from a Japanese wild-type strain isolated from a boy with typical chickenpox named Oka (p-Oka). All commercially distributed vaccines have been reported to differ only in the number of passage of virus in tissue culture used and in stabilizers, as well as other components of the formulation (12)(13)(14)(15)(16). Targeted vaccination of susceptible high-risk patients and/or their household contacts, recommended in many European countries, is an alternative strategy which necessitates a well-organized healthcare system.…”
Section: Vaccinationmentioning
confidence: 99%